Policy Brief for Costa Rica 2021 - Miranda Chacón, Zaray (2021)
Since the 1980s Costa Rica has seen a continuous increase in surface temperatures while precipitation has not registered a consistent signal.1,2 There has not been an increase in water supply, but the rise in temperatures has led to aridity, also increasing potential evaporation in areas such as the northwest of Guanacaste, which has the country’s driest climate. This has led to drier soils, and an increase in the number of forest fires and their health effects, affecting those who work outdoors and are exposed to extreme conditions during the dry season. Heat stress, the working conditions in which heat puts health and safety at risk, causes a direct increase in conditions such as fatigue, heat stroke, and exacerbation of chronic diseases3 during work periods longer than 6 hours.4 Heat stress and dehydration are associated with chronic kidney disease, in manual labourers 4–6 especially in low- and middle-income countries in tropical and subtropical zones.7 For all workers they have negative effects on productivity, and cause poverty and socioeconomic inequity.4 In response to the Paris Agreement and the IPCC report,8 Costa Rica developed a National Policy on Adaptation to Climate Change 2018- 20309 and a National Decarbonization Plan 2018-205010 as tools for adaptation and mitigation. Despite clear policies, progress is slow on key issues, including actions to improve governance. There is a lack of clarity on how sectors and institutions will be integrated towards achieving reported objectives.11 Furthermore, in key areas like transport, Costa Rica has increased its fossil fuel use and ranks third in Latin America in the number of private vehicles per thousand inhabitants